2021
DOI: 10.1101/2021.05.18.444713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3’HS1 CTCF binding site in human β-globin locus regulates fetal hemoglobin expression

Abstract: Mutations in the adult β-globin gene can lead to a variety of hemoglobinopathies, including sickle cell disease and β-thalassemia. An increase in fetal hemoglobin expression throughout adulthood, a condition named Hereditary Persistence of Fetal Hemoglobin (HPFH), has been found to ameliorate hemoglobinopathies. Deletional HPFH occurs through the excision of a significant portion of the 3 prime end of the β-globin locus, including a CTCF binding site termed 3'HS1. Here, we show that the deletion of this CTCF s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…Also OR52A1 gene contains enhancer required for 3′HS1 CTCF binding site in beta-globin for fetal haemoglobin expression (Himadewi et al, 2021). In our study, we found OR52A1 gene with deleterious effect (0.…”
Section: supporting
confidence: 49%
See 1 more Smart Citation
“…Also OR52A1 gene contains enhancer required for 3′HS1 CTCF binding site in beta-globin for fetal haemoglobin expression (Himadewi et al, 2021). In our study, we found OR52A1 gene with deleterious effect (0.…”
Section: supporting
confidence: 49%
“…Individuals with deletion of OR52A1 genes were detected with Beta‐Thalassemia (Van Ziffle, Yang, & Chehab, 2011). Also OR52A1 gene contains enhancer required for 3′HS1 CTCF binding site in beta‐globin for fetal haemoglobin expression (Himadewi et al, 2021). In our study, we found OR52A1 gene with deleterious effect (0.04) had mutation (C > T) in chromosome 15 changing the amino acid sequence and possibly a change in the protein sequence.…”
Section: Discussionmentioning
confidence: 99%
“…2D). Therefore, in addition to HBB KO or producing protein variants because of in-frame INDELs, LDs may induce HbF expression (46)(47)(48), similar to the naturally occurring HPFH. The 13-nt HPFH deletion in the HBG1 promoter has been actively pursued as a treatment strategy for -hemoglobinopathies (27).…”
Section: Discussionmentioning
confidence: 99%